Millennials’ Perspective on Leisure Time - Gajić, Jelena; Brdar, Ivana; Živković, Radmila; Ilić-Petrović, Tamara (Industrija, 2019)
The purpose of this research is to explore leisure time of millennials in Serbia. We have put the content and structure of their ‘free time’ into the focus; moreover, we are interested in how far or how close young people’s freely chosen activities, and relaxing and socializing patterns, are in comparison to other authors’ findings, from the same region, but from other places as well. The results show that some global trends related to the topic are recognized, highly appreciated, and accepted in target population. At the same time, noticeable impact of specific cultural, social, and economic factors is relevant too so that certain local insights should be treated with respect to actual, recent, and even long-lasting local circumstances.